Uncovering the mystery of the atrioventricular node dual-pathway electrophysiology - Shuangtao Ma, MD; James Rail, BS; Youhua Zhang, MD, PhD (Heart Rhythm O2)
With the discovery and validation of a novel index of dual-pathway electrophysiology, known as the His electrogram alternans, major advances have been made in understanding the electrical propagation through the atrioventricular (AV) node. At slow rates, AV conduction starts at the interatrial septal boundary of the node (superior nodal domain) and spreads toward the tricuspid annulus side (inferior nodal domain) in a direction perpendicular to the AV axis and across fiber orientation. Such activation results in an early, superior input into the superior His bundle. This is the fast pathway (FP) conduction. At fast rates, the FP wavefront gradually withdraws from the inferior nodal domain, permitting excitation formed at the crista terminalis end of the node to propagate longitudinally through the inferior nodal domain (also along the fiber orientation) to activate the inferior His bundle. This is the slow pathway (SP) conduction. The failure of FP conduction in the superior nodal domain permits retrograde invasion of the SP wavefront, forming a re-entry, but normally not AV nodal re-entrant tachycardia. The described dual-pathway electrophysiology is a normal inherent property of AV node conduction. The potential electrophysiological basis for a jump in the AV conduction curve and AV nodal re-entrant tachycardia is also discussed.